Tinjauan Yuridis Kesalahan Pengukuran Tanah pada Pendaftaran Tanah di Kabupaten Wajo - Mustafa, Dewi Wahyuni; Rismawati; Muh Farhan Fadhillah; Abdul Madjid (Legal Journal of Law, 2025)
The purpose of this study was to determine the factors that cause errors in land boundary measurements during the land registration process in Wajo Regency and to determine legal remedies for errors in land boundary measurements during the land registration process at the National Land Office of Wajo Regency. This study was conducted at the National Land Agency (BPN) of Wajo Regency using an empirical research approach with data collection through interviews so that the data obtained were analyzed comparatively and presented descriptively. The results of this study indicate that the main factors causing errors in land measurement occur due to the absence of land owners and bordering parties during the measurement, the lack of installation and maintenance of boundary markers, technical errors by surveyors, limited human resources and technology, and inefficient administrative procedures. Community unpreparedness and lack of education also exacerbate this situation. To overcome this problem, a comprehensive approach is needed through improving the service system, increasing technical capacity, and empowering communities to maintain and understand the boundaries of their land rights. Meanwhile, legal resolution efforts for errors in land boundary measurements during the land registration process at the National Land Agency Office in Wajo Regency can be carried out by referring to the Basic Agrarian Law (UUPA) and Government Regulation Number 24 of 1997, Regulation of the Head of the National Land Agency Number 3 of 2011, and other related regulations. Handling land ownership disputes due to errors in boundary determination, one of which is through the courts by revoking land certificates that are proven to have legal administrative defects. This revocation must be based on definite evidence. In addition to going through the courts, in resolving disputes, the applicant and related parties can be involved in finding a joint solution